Analisis Pemberitaan Perceraian Gading Marten dan Gisella Anastasia pada Serambinews.com - Salamah, Khoirina Nur (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2022)
Gading Marteen and Gisella Anastasia are among the artists who rarely reported with negative issues, but in 2018 news of Gisella Anastasia's divorce lawsuit against Gading Marteen was widely reported, one of which was on the online media Serambinews.com with the title Ibu Gempita ‘Gisel’ Ingin Rujuk, Gading Marten Diwanti-wanti Ini: Jangan Artis, ‘Ribet’, published on Tuesday, September 22, 2020 at 22:47 . The purpose of this research is to find out the meanings contained in the writing of a news report on the divorce of Gading Marteen and Gisella Anastasia in the online news media Serambinews. This research uses Norman Fairclough's discourse analysis which contains three dimensions, namely text (microstructural), discourse (mesostructural), and sociocultural (macrostructural) which were developed to produce news in the mass media. The results show that Serambinews.com uses clear and striking word choices and uses interview quotes from various sources. In this case, Serambinews.com also leads readers to judge Gading Marten and Gisella Anastasia, although there is a tendency for Gisel to be shown negatively and Gading to be positive.